2015
DOI: 10.1177/1090198115598986
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Sexual Communication Self-Efficacy Scale

Abstract: This study assessed a newly developed Sexual Communication Self-Efficacy Scale designed to measure the sexual communication self-efficacy of adolescent men and women. Three-hundred and seventy-four U.K. adolescents completed this new scale, along with several other validity measures. Factor analysis revealed that the Sexual Communication Self-Efficacy Scale consisted of five underlying factors: contraception communication, positive sexual messages, negative sexual messages, sexual history, and condom negotiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…Most items in Levinson's scale are not relevant to nonadolescent women in low-resource settings as they pertain to adolescent-specific subjects such as parental knowledge of contraceptive use. There are validated scales to measure self-efficacy for condom use, sexual communication and protective sexual behaviors [ [6] , [7] , [8] , [9] ]. However, review of the literature revealed no appropriate standardized tool to measure CSE in low-resource settings such as sub-Saharan Africa (SSA).…”
Section: Introductionmentioning
confidence: 99%
“…Most items in Levinson's scale are not relevant to nonadolescent women in low-resource settings as they pertain to adolescent-specific subjects such as parental knowledge of contraceptive use. There are validated scales to measure self-efficacy for condom use, sexual communication and protective sexual behaviors [ [6] , [7] , [8] , [9] ]. However, review of the literature revealed no appropriate standardized tool to measure CSE in low-resource settings such as sub-Saharan Africa (SSA).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, results concerning exercise of choice warrant further refinement of current women's sexual empowerment quantitative measures. Instrument items to measure self-efficacy have traditionally focused on verbal communication (Quinn-Nilas et al 2016;Pearson 2006); however, the results of this study highlight the need to also measure non-verbal actions to comprehensively capture the decision-making and negotiation processes central to women's exercise of choice. Across settings, women described difficulty in verbally articulating their preferences, using non-verbal communication instead to do so (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The implications of women's empowerment for SRH are also complicated by the fact that empowerment relates to capabilities across multiple dimensions, involving rights and participation in civil, political, socio-economic and cultural domains. More targeted research has specifically focused on the process of SRH empowerment using concepts of sexual self-efficacy (Quinn-Nilas et al 2016), sexual assertiveness (Morokoff et al 1997), sexual power (Pulerwitz, Gortmaker, and DeJong 2000) and reproductive autonomy (Upadhyay et al 2014), to better capture the gender dynamics shaping women's sexual decisions and outcomes. This rich body of research, however, is difficult to synthesise in the absence of a comprehensive framework relating these constructs to one another.…”
mentioning
confidence: 99%
“…Data will be collected using a number of standardised measures, including comfort communicating about pregnancy and comfort communicating about contraception derived from mathtech behaviour inventory 65 ; the male role attitudes scale 66 ; sexual socialisation instrument 67 and sexual self-efficacy scale. 68 We will also collect data using an ‘intentions to avoid a teenage pregnancy scale’, developed and psychometrically tested in our feasibility trial. 43 The measures were selected because the constructs they measure map closely to the theoretical framework underpinning the intervention and the reliability and completion rates of the measures were satisfactory in the feasibility trial.…”
Section: Methods and Analysismentioning
confidence: 99%